Molecular basis for enantioselectivity in the (R)- and (S)-hydroxypropylthioethanesulfonate dehydrogenases, a unique pair of stereoselective short-chain dehydrogenases/reductases involved in aliphatic epoxide carboxylation - Sliwa, Dariusz A. (2010)
(R)- and (S)-2-hydroxypropyl-CoM (R-HPC and S-HPC) are produced as intermediates in bacterial propylene metabolism from the nucleophilic addition of coenzyme M to (R)- and (S)-epoxypropane, respectively. Two highly enantioselective dehydrogenases (R-HPCDH and S-HPCDH) belonging to the short-chain dehydrogenase/reductase family catalyze the conversion of R-HPC and S-HPC to 2-ketopropyl-CoM (2-KPC), which undergoes reductive cleavage and carboxylation to produce acetoacetate. In the present study, one of three copies of S-HPCDH enzymes present on a linear megaplasmid in Xanthobacter autotrophicus strain Py2 has been cloned and overexpressed, allowing the first detailed side by side characterization of the R-HPCDH and S-HPCDH enzymes. The catalytic triad of S-HPCDH was found to consist of Y156, K160, and S143. R211 and K214 were identified as the amino acid residues coordinating the sulfonate of CoM in S-HPC. R211A and K214A mutants were severely impaired in the oxidation of R-HPC or reduction of 2-KPC but were largely unaffected in the oxidation and reduction of aliphatic alcohols and ketones. Kinetic analyses using (R)- and (S)-HPC as substrates revealed that enantioselectivity in R-HPCDH (value, 944) was dictated largely by differences in k(cat) while enantioselectivity for S-HPCDH (value, 658) was dictated largely by changes in K(m). S-HPCDH had an inherent high enantioselectivity for producing (S)-2-butanol from 2-butanone that was unaffected by modulators that interact with the sulfonate binding site. The tertiary alcohol 2-methyl-2-hydroxypropyl-CoM (M-HPC) was a competitive inhibitor of R-HPCDH-catalyzed R-HPC oxidation, with a K(is) similar to the K(m) for R-HPC, but was not an inhibitor of S-HPCDH. The primary alcohol 2-hydroxyethyl-CoM was a substrate for both R-HPCDH and S-HPCDH with identical K(m) values. The pH dependence of kinetic parameters suggests that the hydroxyl group is a larger contributor to S-HPC binding to S-HPCDH than for R-HPC binding to R-HPCDH. It is proposed that active site constraints within the S-HPCDH prevent proper binding of R-HPC and M-HPC due to steric clashes with the improperly aligned methyl group on the C2 carbon, resulting in a different mechanism for controlling substrate specificity and enantioselectivity than present in the R-HPCDH.